Consolidation of cellular memory representations in superficial neocortex - Ingrid M. Esteves; HaoRan Chang; Adam R. Neumann; Bruce L. McNaughton (iScience, 2023)
Summary: Systems-level memory consolidation, a key concept in memory research, involves the conversion of memories that depend on the hippocampus for their formation into efficient hippocampus-independent forms, presumably encoded by cortico-cortical connections. Yet, little is understood about the nature of consolidated neural codes at the cellular ensemble level. Mice require an intact hippocampus for “virtual” spatial learning and to develop neocortical representations of the corresponding experiences. We find that, whereas a novel virtual environment is neither learned nor represented in superficial cortex following severe damage to hippocampus, pre-operatively learned memories and their corresponding sparse and widespread neural ensemble representations in cortical layers II–III are preserved, a sine qua non of memory consolidation. These findings provide a new window for future study of the cellular mechanisms of memory consolidation.